(untitled) (Junior Management Science, 2018)
The urge for firms to contribute positively towards the society and the environment is increasing significantly. Demands of employees, customers, governments, NGOs and many more are putting firms under pressure to respond accordingly. Thus, it is vital for firms nowadays to formulate effective corporate social responsibility (CSR) strategies which provide guidelines for the firm’s commitment towards the challenges of the society and environment. Plenty of research exists on the components of CSR strategy formulation, particularly regarding stakeholders, organizational vision and the CEO’s influence. However, it is important to consider the whole process of the strategy formulation and to link the components together. By means of a qualitative analytical approach, I show that the internal input provided by the CEO and the CSR team plays an important role in deciding on certain CSR initiatives. Furthermore, the strategic fit between the potential CSR issues and the core business is a significant criterion. Through assessing the potential value creation, and thus the expected impact scope, prioritizations of CSR issues take place. The continuous monitoring and evaluation of the stakeholders’ needs form an iterative process which leads to a constantly changing CSR strategy focus of the firm. My aim in this paper is to contribute to the understanding of CSR strategy formulation through a CSR strategy formulation process model. The model provides insights into firms’ CSR strategy formulation from which I derive implications for management and further research. Keywords: Corporate Social Responsibility, Strategy Formulation, Sustainability